Representing Women’s Interests in Japan’s Civil Society - Sae Okura (Societies, 2021)
Japan has witnessed marginalization and underrepresentation of women in its civil society. This study examines its extent. It also explores who in Japan’s civil society represent women’s interests by using survey data from civil society organizations. This study reveals that civil society organizations are generally led by male leaders, and around half of their staff are male. It also indicates that the number of organizations representing women’s interests is limited, with only 2.2% representing women’s interests. Interestingly, the central actors representing women’s interests include economic and business groups, political groups, labor groups, and civic groups including women’s groups.